Environment-sensitive hydrogels for drug delivery - Qiu, Yong; Park, Kinam (Advanced drug delivery reviews, 2012)
Environmentally sensitive hydrogels have enormous potential in various applications. Some environmental variables, such as low pH and elevated temperatures, are found in the body. For this reason, either pH-sensitive and/or temperature-sensitive hydrogels can be used for site-specific controlled drug delivery. Hydrogels that are responsive to specific molecules, such as glucose or antigens, can be used as biosensors as well as drug delivery systems. Light-sensitive, pressure-responsive and electro-sensitive hydrogels also have the potential to be used in drug delivery and bioseparation. While the concepts of these environment-sensitive hydrogels are sound, the practical applications require significant improvements in the hydrogel properties. The most significant weakness of all these external stimuli-sensitive hydrogels is that their response time is too slow. Thus, fast-acting hydrogels are necessary, and the easiest way of achieving that goal is to make thinner and smaller hydrogels. This usually makes the hydrogel systems too fragile and they do not have mechanical strength necessary in many applications. Environmentally sensitive hydrogels for drug delivery applications also require biocompatibility. Synthesis of new polymers and crosslinkers with more biocompatibility and better biodegradability would be essential for successful applications. Development of environmentally sensitive hydrogels with such properties is a formidable challenge. If the achievements of the past can be extrapolated into the future, however, it is highly likely that responsive hydrogels with a wide array of desirable properties can be made.